The Governance of Inter-firm Co-development Projects in an Open Innovation Setting - Biswas,Sharlene; Akroyd,Chris (Pacific Accounting Review, 2016)
Purpose - This paper examines the governance of inter-firm co-development in an open innovation setting and shows how a stage-gate product development process can be used to support this relationship. Design/methodology/approach - We adopt a qualitative case-study approach informed by ethnomethodology. Data was obtained via semi-structured interviews and document analysis. Findings - We found that in an open innovation setting - where the producing partner relies on a research partner for all product development activities - a stage-gate product development process can act as a governance mechanism as it enables the development of trust and cooperation which supports the co-development relationship. Research limitations/implications - The implication of this finding is that a stage-gate process can be a flexible governance mechanism, which can adapt over time in relation to the needs of the co-development partners in an open innovation setting. This also lays the groundwork for future research to explore the applicability of this tool in other settings e.g. outsourcing arrangements as well as help guide the design and implementation of future governance mechanisms. Originality/value - In the context of accounting research, this paper helps practitioners and academics understand how a stage-gate process can be used as a governance mechanism to manage and control co-development projects in an open innovation setting.
Keywords: Accounting